Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Lineage specific histories of Mycobacterium tuberculosis dispersal in Africa and Eurasia - Mary B. O'Neill; Abigail Shockey; Alex Zarley; William Aylward; Vegard Eldholm; Andrew Kitchen; Caitlin S. Pepperell (Molecular Ecology, 2019)
Mycobacterium tuberculosis ( M.tb ) is a globally distributed, obligate pathogen of humans that can be divided into seven clearly defined lineages. An emerging consensus places the origin and global dispersal of M.tb within the past 6,000 years: identifying how the ancestral clone of M.tb spread and differentiated within this timeframe is important for identifying the ecological drivers of the current pandemic. We used Bayesian phylogeographic inference to reconstruct the migratory history of M.tb in Africa and Eurasia and to investigate lineage specific patterns of spread from a geographically diverse sample of 552 M.tb genomes. Applying evolutionary rates inferred with ancient M.tb genome calibration, we estimated the timing of major events in the migratory history of the pathogen. Inferred timings contextualize M.tb dispersal within historical phenomena that altered patterns of connectivity throughout Africa and Eurasia: trans‐Indian Ocean trade in spices and other goods, the Silk Road and its predecessors, the expansion of the Roman Empire, and the European Age of Exploration. We found that Eastern Africa and Southeast Asia have been critical in the dispersal of M.tb . Our results further reveal that M.tb populations have grown through range expansion, as well as in situ, and delineate the independent evolutionary trajectories of bacterial subpopulations underlying the current pandemic.

Scombroid Fishes Provide Novel Insights into the Trait/Rate Associations of Molecular Evolution - Fan Qiu; Andrew Kitchen; J. Gordon Burleigh; Michael M. Miyamoto (Journal of Molecular Evolution, 2014)

The Evolutionary Dynamics of Bluetongue Virus - Giovanna Carpi; Edward C. Holmes; Andrew Kitchen (Journal of Molecular Evolution, 2010)

Coprological Surveys of Alouatta pigra at Two Sites in Belize - Katherine A. Eckert; Nina E. Hahn; Andrew Genz; Dawn M. Kitchen; Michael D. Stuart; Gary A. Averbeck; Bert E. Stromberg; Hal Markowitz (International Journal of Primatology, 2006)